A method for preparing zwitterionic fracturing thickener

By modifying the guar gum and adding a composite crosslinking agent, the zwitterionic fracturing thickener was prepared, which solved the problems of low viscosity, insufficient shear resistance and insufficient temperature resistance of the existing thickener, and achieved higher viscosity, shear resistance and temperature resistance.

CN119264898BActive Publication Date: 2025-04-15CHIFENG AOLONG CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411789025.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-15
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing fracturing thickeners have low viscosity, insufficient shear resistance, poor sand carrying effect, and insufficient temperature resistance, making it difficult to meet the needs of deep and ultra-deep well construction.

Method used

A zwitterionic fracturing thickening agent is prepared by modifying the guar gum and adding a composite crosslinking agent. The method includes grafting guar gum using a reaction of epoxy groups and hydroxyl groups, introducing a benzene ring structure and an unsaturated carbon long chain, and introducing a zwitterionic structure through a click reaction of sulfhydryl groups and double bonds, while combining the unique structure of the composite crosslinking agent with the guar gum matrix to form a crosslinking system.

Benefits of technology

It significantly improves the viscosity, shear resistance and temperature resistance of the thickener, improves the sand carrying effect, and can better adapt to the needs of deep and ultra-deep well construction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fracturing thickeners, and in particular to a method for preparing a zwitterionic fracturing thickener. The zwitterionic fracturing thickener comprises the following raw materials in weight percentage: 35-40% carboxymethyl guar gum, 5-8% carboxymethyl hydroxypropyl guar gum, 15-20% composite guar gum and 6-8% composite cross-linking agent, and the balance is water. The guar gum is modified and the composite cross-linking agent is added, thereby solving the problems of low viscosity, insufficient shear resistance and poor sand carrying effect of the existing fracturing thickener, and greatly improving the temperature resistance thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fracturing thickeners, and in particular to a method for preparing a zwitterionic fracturing thickener. Background Art

[0002] Thickener is the main additive of water-based fracturing fluid. Its performance has an important influence on the comprehensive performance of fracturing fluid and the fracturing construction effect. There are many types of water-based fracturing fluid thickeners commonly used, which are mainly divided into two categories: pure natural thickeners and their modified thickeners and polymer thickeners.

[0003] The main base materials of the currently commonly used natural thickeners are biomacromolecules such as starch, fiber and guar gum. Among them, carboxymethyl guar gum is a commonly used thickener on the market. It has good solubility and thickening effect. However, it has problems such as low viscosity, insufficient shear resistance and poor sand carrying effect during use. At the same time, with the increasing number of deep and ultra-deep well construction, the construction temperature of fracturing fluid has generally increased, which has also put forward new requirements for the temperature resistance of thickeners. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a zwitterionic fracturing thickener, which solves the problems of low viscosity, insufficient shear resistance and poor sand carrying effect of the existing fracturing thickener by modifying guar gum and adding a composite crosslinking agent, and greatly improves its temperature resistance.

[0005] The purpose of the present invention can be achieved by the following technical scheme: a method for preparing a zwitterionic fracturing thickener, comprising the following steps: weighing the following raw materials in weight percentage: 35-40% carboxymethyl guar gum, 5-8% carboxymethyl hydroxypropyl guar gum, 15-20% composite guar gum and 6-8% composite cross-linking agent, the balance being water, and mixing the carboxymethyl guar gum, carboxymethyl hydroxypropyl guar gum, composite guar gum, composite cross-linking agent and water to prepare a zwitterionic fracturing thickener;

[0006] The composite guar gum is prepared by the following steps:

[0007] Step A1: Mix cardanol, sodium hydroxide solution, tetrabutylammonium bromide and toluene, stir at a stirring rate of 150-180 rpm and a temperature of 70°C, add epichlorohydrin, and react for 4-6 hours to obtain intermediate 1; mix guar gum, sodium hydroxide solution and anhydrous ethanol, stir at a stirring rate of 80-120 rpm and room temperature for 20 minutes, add intermediate 1, and heat to 70°C and react for 6-8 hours to obtain grafted guar gum;

[0008] The mass fraction of sodium hydroxide solution is 30%, and the amount ratio of cardanol, sodium hydroxide solution, tetrabutylammonium bromide and epichlorohydrin is 0.02-0.022 mol: 3-3.2 mL: 0.12-0.13 g: 0.022-0.024 mol; the mass fraction of sodium hydroxide solution is 30%, and the amount ratio of guar gum, sodium hydroxide solution and intermediate 1 is 10-12 g: 6-8 mL: 0.02-0.022 mol;

[0009] During the reaction, under the condition of tetrabutylammonium bromide as a catalyst, epichlorohydrin and phenolic hydroxyl groups in cardanol undergo a ring-opening reaction to generate hydroxyl groups, which then react with chlorine under alkaline conditions to form epoxy groups, thereby obtaining an intermediate 1 containing epoxy groups, and the epoxy groups in the intermediate 1 then react with hydroxyl groups in guar gum to etherify and form new hydroxyl groups, thereby obtaining grafted guar gum;

[0010] Step A2: 2,5-dimercaptothiadiazole and ethyl acetate are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 100°C, 1,3-propane sultone is added, and the mixture is reacted for 24 hours to obtain intermediate 2; intermediate 2, grafted guar gum, ethanol and deionized water are mixed, stirred at a stirring rate of 60-80 rpm and room temperature, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is added, and the mixture is reacted for 12 hours under light conditions to obtain modified guar gum;

[0011] The amount ratio of 2,5-dimercaptothiadiazole, ethyl acetate and 1,3-propane sultone is 0.02-0.022 mol: 30-34 mL: 0.045-0.048 mol; the amount ratio of intermediate 2, grafted guar gum and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is 12-13 g: 0.01-0.011 mol: 0.8-1 g;

[0012] During the reaction, 2,5-dimercaptothiadiazole and 1,3-propane sultone undergo a ring-opening reaction to form a quaternary ammonium structure and generate a sulfonic acid group to obtain intermediate 2. Then, under the condition of 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone as an initiator, the thiol group in intermediate 2 and the double bond in the cardanol structure in the grafted guar gum undergo a click reaction to obtain modified guar gum.

[0013] Step A3: Modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide are mixed, stirred at a stirring rate of 120-150 rpm and room temperature, and lipoic acid is added, and the mixture is reacted for 24 hours to obtain composite guar gum;

[0014] The ratio of modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and lipoic acid is 12-13 g: 5-6 g: 8-10 g: 0.01-0.012 mol;

[0015] During the reaction, under the action of 4-dimethylaminopyridine and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, the hydroxyl group in the modified guar gum and the carboxyl group in the lipoic acid undergo esterification reaction to obtain the composite guar gum.

[0016] The composite cross-linking agent is prepared by the following steps:

[0017] Step B1: Mix silica nanospheres and anhydrous ethanol and ultrasonically disperse for 30 minutes, stir and add ammonia solution and tetrabutyl titanate at a stirring rate of 150-180 rpm and a temperature of 45°C, and react for 24 hours to obtain precursor 1, and mix precursor 1, hexadecyltrimethylammonium bromide and deionized water, stir for 12 hours at a stirring rate of 120-150 rpm and a temperature of 60°C to obtain precursor 2;

[0018] The mass fraction of ammonia solution is 25%, the amount ratio of silica nanospheres, ammonia solution and tetrabutyl titanate is 0.3-0.4g:1.2-1.4mL:3.8-4mL; the amount ratio of precursor 1 and hexadecyltrimethylammonium bromide is 0.4-0.5g:0.16-0.2g;

[0019] During the reaction, a titanium oxide layer is formed on the surface of the silica nanospheres by a hydrothermal method using silica nanospheres as a hard template and tetrabutyl titanate as a titanium source to obtain a precursor 1. The precursor 1 is then mixed with hexadecyltrimethylammonium bromide to modify the titanium oxide layer on the surface to obtain a precursor 2.

[0020] Step B2: Precursor 2, sodium molybdate dihydrate, thioacetamide and deionized water are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 60°C for 12 hours, and then heated to 220°C for further reaction for 24 hours to obtain precursor 3, precursor 3 is mixed with deionized water and ultrasonically dispersed for 20 minutes, stirred at a stirring rate of 120-150 rpm and room temperature, and sodium hydroxide solution is added and stirred for 6-8 hours to obtain precursor 4, and precursor 4 is calcined at 600°C for 2 hours to obtain a composite crosslinking agent;

[0021] The amount ratio of precursor 2, sodium molybdate dihydrate and thioacetamide is 0.3-0.4g: 0.12-0.13g: 0.13-0.14g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 3 and sodium hydroxide solution is 0.4-0.45g: 3-4mL;

[0022] During the reaction, when stirred at 60° C., thioacetamide is adsorbed on the surface of precursor 2 due to the presence of hydrogen bonds between the amide group in thioacetamide and the hydroxyl group of the titanium oxide layer. Then, at a temperature of 220° C., thioacetamide is decomposed and fixed on the surface of precursor 2, thereby forming a molybdenum disulfide nanosheet layer to obtain precursor 3. Precursor 3 is then alkali-washed with a sodium hydroxide solution, and the silicon dioxide nanosphere core inside the precursor 3 is selectively corroded to form a hollow mesoporous structure. At the same time, due to the grafting of hexadecyltrimethylammonium bromide, defect sites appear in the molybdenum disulfide nanosheet layer after alkali washing, thereby obtaining precursor 4, which is then calcined to obtain a composite cross-linking agent.

[0023] Beneficial effects of the invention: The invention discloses a method for preparing a zwitterionic fracturing thickener, which solves the problems of low viscosity, insufficient shear resistance and poor sand carrying effect of the existing fracturing thickener by modifying guar gum and adding a composite cross-linking agent, and greatly improves its heat resistance; the intermediate 1 is grafted onto the guar gum by the reaction of epoxy group and hydroxyl group, and a benzene ring structure and an unsaturated carbon long chain are introduced, and then a precursor 2 containing a zwitterionic structure is introduced by a click reaction of thiol group and double bond, and due to the presence of the zwitterionic structure and the carbon long chain structure, it has good amphoteric hydrophobic properties, thereby forming an association between hydrophobic chains, enhancing its shear resistance and temperature resistance, and due to the addition of A composite cross-linking agent is prepared. Due to the presence of molybdenum disulfide nanosheets containing defective sites on the surface of the composite cross-linking agent, it forms a unique sphere-sheet structure with the hollow mesoporous titanium oxide. Due to the presence of unreacted thiol groups and thioctic acid groups in the composite guar gum, it can not only self-cross-link to form disulfide bonds, but also covalently bond with the molybdenum disulfide nanosheets containing defective sites. At the same time, the guar gum itself can also combine with the hollow mesoporous titanium oxide, which makes the composite cross-linking agent serve as a cross-linking site to form a cross-linking system. Due to its special structure, it can better combine with the guar gum matrix, thereby forming a shielding effect inside the thickener, reducing the damage to the guar gum molecular chain caused by high temperature, and improving the temperature resistance of the thickener. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1 A method for preparing a zwitterionic fracturing thickener comprises the following steps: weighing the following raw materials in weight percentage: 35% of commercially available Guangpu carboxymethyl guar gum, 8% of commercially available Guangpu carboxymethyl hydroxypropyl guar gum, 15% of composite guar gum and 6-8% of composite cross-linking agent, the balance being water, mixing the carboxymethyl guar gum, carboxymethyl hydroxypropyl guar gum, composite guar gum, composite cross-linking agent and water to prepare a zwitterionic fracturing thickener;

[0026] The composite guar gum is prepared by the following steps:

[0027] Step A1: Mix cardanol, sodium hydroxide solution, tetrabutylammonium bromide and toluene, stir at a stirring rate of 150 rpm and a temperature of 70°C, add epichlorohydrin, and react for 4 hours to obtain intermediate 1; mix commercially available Guangpu guar gum, sodium hydroxide solution and anhydrous ethanol, stir at a stirring rate of 80 rpm and room temperature for 20 minutes, add intermediate 1, and heat to 70°C and react for 6 hours to obtain grafted guar gum;

[0028] The mass fraction of sodium hydroxide solution is 30%, and the amount ratio of cardanol, sodium hydroxide solution, tetrabutylammonium bromide and epichlorohydrin is 0.02mol: 3mL: 0.13g: 0.022mol; the mass fraction of sodium hydroxide solution is 30%, and the amount ratio of guar gum, sodium hydroxide solution and intermediate 1 is 10g: 6mL: 0.02mol;

[0029] Step A2: 2,5-dimercaptothiadiazole and ethyl acetate were mixed, stirred at a stirring rate of 120 rpm and a temperature of 100°C, 1,3-propane sultone was added, and the mixture was reacted for 24 hours to obtain intermediate 2; intermediate 2, grafted guar gum, ethanol and deionized water were mixed, stirred at a stirring rate of 60 rpm and room temperature, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was added, and the mixture was reacted for 12 hours under light conditions to obtain modified guar gum;

[0030] The ratio of 2,5-dimercaptothiadiazole, ethyl acetate and 1,3-propane sultone was 0.022 mol: 30 mL: 0.045 mol; the ratio of intermediate 2, grafted guar gum and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was 12 g: 0.01 mol: 0.8 g;

[0031] Step A3: Modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide were mixed, stirred at a stirring rate of 120 rpm and room temperature, and lipoic acid was added, and the mixture was reacted for 24 hours to obtain composite guar gum;

[0032] The ratio of modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and lipoic acid is 12g:5g:8g:0.01mol;

[0033] The composite cross-linking agent is prepared by the following steps:

[0034] Step B1: Mix commercially available Zhongke Keyou silica nanospheres and anhydrous ethanol and ultrasonically disperse them for 30 minutes, stir and add ammonia solution and tetrabutyl titanate at a stirring rate of 150 rpm and a temperature of 45°C, and react for 24 hours to obtain precursor 1, and mix precursor 1, hexadecyltrimethylammonium bromide and deionized water, stir for 12 hours at a stirring rate of 120 rpm and a temperature of 60°C to obtain precursor 2;

[0035] The mass fraction of ammonia solution is 25%, the amount ratio of silica nanospheres, ammonia solution and tetrabutyl titanate is 0.3g:1.2mL:3.8mL; the amount ratio of precursor 1 and hexadecyltrimethylammonium bromide is 0.4g:0.16g;

[0036] Step B2: Precursor 2, sodium molybdate dihydrate, thioacetamide and deionized water were mixed, stirred at a stirring rate of 120 rpm and a temperature of 60°C for 12 hours, and then heated to 220°C for further reaction for 24 hours to obtain precursor 3, precursor 3 was mixed with deionized water and ultrasonically dispersed for 20 minutes, stirred at a stirring rate of 120 rpm and room temperature, and sodium hydroxide solution was added and stirred for 6 hours to obtain precursor 4, and precursor 4 was calcined at 600°C for 2 hours to obtain a composite crosslinking agent;

[0037] The amount ratio of precursor 2, sodium molybdate dihydrate and thioacetamide is 0.3g:0.12g:0.13g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 3 and sodium hydroxide solution is 0.4g:3mL.

[0038] Example 2 A method for preparing a zwitterionic fracturing thickener comprises the following steps: weighing the following raw materials in weight percentage: 35% of commercially available Guangpu carboxymethyl guar gum, 5% of commercially available Guangpu carboxymethyl hydroxypropyl guar gum, 20% of composite guar gum and 6% of composite cross-linking agent, the remainder being water, mixing the carboxymethyl guar gum, carboxymethyl hydroxypropyl guar gum, composite guar gum, composite cross-linking agent and water to prepare a zwitterionic fracturing thickener;

[0039] The composite guar gum is prepared by the following steps:

[0040] Step A1: Mix cardanol, sodium hydroxide solution, tetrabutylammonium bromide and toluene, stir at a stirring rate of 180 rpm and a temperature of 70°C, add epichlorohydrin, and react for 4 hours to obtain intermediate 1; mix commercially available Guangpu guar gum, sodium hydroxide solution and anhydrous ethanol, stir at a stirring rate of 80 rpm and room temperature for 20 minutes, add intermediate 1, and heat to 70°C and react for 8 hours to obtain grafted guar gum;

[0041] The mass fraction of sodium hydroxide solution is 30%, and the amount ratio of cardanol, sodium hydroxide solution, tetrabutylammonium bromide and epichlorohydrin is 0.02mol: 3mL: 0.13g: 0.022mol; the mass fraction of sodium hydroxide solution is 30%, and the amount ratio of guar gum, sodium hydroxide solution and intermediate 1 is 10g: 6mL: 0.022mol;

[0042] Step A2: 2,5-dimercaptothiadiazole and ethyl acetate were mixed, stirred at a stirring rate of 120 rpm and a temperature of 100°C, 1,3-propane sultone was added, and the mixture was reacted for 24 hours to obtain intermediate 2; intermediate 2, grafted guar gum, ethanol and deionized water were mixed, stirred at a stirring rate of 80 rpm and room temperature, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was added, and the mixture was reacted for 12 hours under light conditions to obtain modified guar gum;

[0043] The ratio of 2,5-dimercaptothiadiazole, ethyl acetate and 1,3-propane sultone was 0.02 mol: 34 mL: 0.045 mol; the ratio of intermediate 2, grafted guar gum and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was 12 g: 0.01 mol: 1 g;

[0044] Step A3: Modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide were mixed, stirred at a stirring rate of 120 rpm and room temperature, and lipoic acid was added, and the mixture was reacted for 24 hours to obtain composite guar gum;

[0045] The ratio of modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and lipoic acid is 12g:6g:10g:0.01mol;

[0046] The composite cross-linking agent is prepared by the following steps:

[0047] Step B1: Mix commercially available Zhongke Keyou silica nanospheres and anhydrous ethanol and ultrasonically disperse them for 30 minutes, stir and add ammonia solution and tetrabutyl titanate at a stirring rate of 180 rpm and a temperature of 45°C, and react for 24 hours to obtain precursor 1, and mix precursor 1, hexadecyltrimethylammonium bromide and deionized water, stir for 12 hours at a stirring rate of 120 rpm and a temperature of 60°C to obtain precursor 2;

[0048] The mass fraction of ammonia solution is 25%, the amount ratio of silica nanospheres, ammonia solution and tetrabutyl titanate is 0.3g:1.2mL:4mL; the amount ratio of precursor 1 and hexadecyltrimethylammonium bromide is 0.4g:0.2g;

[0049] Step B2: Precursor 2, sodium molybdate dihydrate, thioacetamide and deionized water were mixed, stirred at a stirring rate of 120 rpm and a temperature of 60°C for 12 hours, and then heated to 220°C for further reaction for 24 hours to obtain precursor 3, precursor 3 was mixed with deionized water and ultrasonically dispersed for 20 minutes, stirred at a stirring rate of 150 rpm and room temperature, and sodium hydroxide solution was added and stirred for 6 hours to obtain precursor 4, and precursor 4 was calcined at 600°C for 2 hours to obtain a composite crosslinking agent;

[0050] The amount ratio of precursor 2, sodium molybdate dihydrate and thioacetamide is 0.4g:0.12g:0.14g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 3 and sodium hydroxide solution is 0.45g:3mL.

[0051] Example 3 A method for preparing a zwitterionic fracturing thickener comprises the following steps: weighing the following raw materials in weight percentage: 40% of commercially available Guangpu carboxymethyl guar gum, 8% of commercially available Guangpu carboxymethyl hydroxypropyl guar gum, 20% of composite guar gum and 8% of composite cross-linking agent, the remainder being water, mixing the carboxymethyl guar gum, carboxymethyl hydroxypropyl guar gum, composite guar gum, composite cross-linking agent and water to prepare a zwitterionic fracturing thickener;

[0052] The composite guar gum is prepared by the following steps:

[0053] Step A1: Mix cardanol, sodium hydroxide solution, tetrabutylammonium bromide and toluene, stir at a stirring rate of 180 rpm and a temperature of 70°C, add epichlorohydrin, and react for 6 hours to obtain intermediate 1; mix commercially available Guangpu guar gum, sodium hydroxide solution and anhydrous ethanol, stir at a stirring rate of 120 rpm and room temperature for 20 minutes, add intermediate 1, and heat to 70°C and react for 8 hours to obtain grafted guar gum;

[0054] The mass fraction of sodium hydroxide solution is 30%, and the amount ratio of cardanol, sodium hydroxide solution, tetrabutylammonium bromide and epichlorohydrin is 0.022 mol: 3.2 mL: 0.13 g: 0.024 mol; the mass fraction of sodium hydroxide solution is 30%, and the amount ratio of guar gum, sodium hydroxide solution and intermediate 1 is 12 g: 8 mL: 0.022 mol;

[0055] Step A2: 2,5-dimercaptothiadiazole and ethyl acetate were mixed, stirred at a stirring rate of 150 rpm and a temperature of 100°C, 1,3-propane sultone was added, and the mixture was reacted for 24 hours to obtain intermediate 2; intermediate 2, grafted guar gum, ethanol and deionized water were mixed, stirred at a stirring rate of 80 rpm and room temperature, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was added, and the mixture was reacted for 12 hours under light conditions to obtain modified guar gum;

[0056] The ratio of 2,5-dimercaptothiadiazole, ethyl acetate and 1,3-propane sultone was 0.022 mol: 34 mL: 0.048 mol; the ratio of intermediate 2, grafted guar gum and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone was 13 g: 0.011 mol: 1 g;

[0057] Step A3: Modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide were mixed, stirred at a stirring rate of 150 rpm and room temperature, and lipoic acid was added, and the mixture was reacted for 24 hours to obtain composite guar gum;

[0058] The ratio of modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and lipoic acid is 13 g: 6 g: 10 g: 0.012 mol;

[0059] The composite cross-linking agent is prepared by the following steps:

[0060] Step B1: Mix commercially available Zhongke Keyou silica nanospheres and anhydrous ethanol and ultrasonically disperse them for 30 minutes, stir and add ammonia solution and tetrabutyl titanate at a stirring rate of 180 rpm and a temperature of 45°C, and react for 24 hours to obtain precursor 1, and mix precursor 1, hexadecyltrimethylammonium bromide and deionized water, and stir for 12 hours at a stirring rate of 150 rpm and a temperature of 60°C to obtain precursor 2;

[0061] The mass fraction of ammonia solution was 25%, the amount ratio of silica nanospheres, ammonia solution and tetrabutyl titanate was 0.4 g: 1.4 mL: 4 mL; the amount ratio of precursor 1 and hexadecyltrimethylammonium bromide was 0.5 g: 0.2 g;

[0062] Step B2: Precursor 2, sodium molybdate dihydrate, thioacetamide and deionized water were mixed, stirred at a stirring rate of 150 rpm and a temperature of 60°C for 12 hours, and then heated to 220°C for further reaction for 24 hours to obtain precursor 3, precursor 3 was mixed with deionized water and ultrasonically dispersed for 20 minutes, stirred at a stirring rate of 150 rpm and room temperature, and sodium hydroxide solution was added and stirred for 8 hours to obtain precursor 4, and precursor 4 was calcined at 600°C for 2 hours to obtain a composite crosslinking agent;

[0063] The amount ratio of precursor 2, sodium molybdate dihydrate and thioacetamide is 0.4g:0.13g:0.14g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 3 and sodium hydroxide solution is 0.45g:4mL.

[0064] Comparative Example 1 Compared with Example 3, this comparative example is different in that the composite guar gum in the preparation process of the zwitterionic fracturing thickener in Example 3 is replaced by modified guar gum, and the other steps are the same.

[0065] Comparative Example 2 Compared with Example 3, this comparative example is different in that the intermediate 2 in the preparation process of the modified guar gum in Example 3 is replaced by 2,5-dimercaptothiadiazole, and the other steps are the same.

[0066] Comparative Example 3 Compared with Example 3, this comparative example replaces the composite cross-linking agent in the preparation process of the zwitterionic fracturing thickener in Example 3 with a mixture of commercially available Mister titanium oxide and commercially available Hongtai molybdenum disulfide, and the other steps are the same, wherein the mass ratio of titanium oxide to molybdenum disulfide is 5g:1g.

[0067] Take the zwitterionic fracturing thickeners prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, add 4 g of zwitterionic fracturing thickener, 1 g of sodium tetraborate, 9 g of commercially available RD-15 clay stabilizer and 3.8 g of commercially available ER-100 drainage agent to 1000 mL of water, stir at room temperature for 20 min to prepare a fracturing system, and perform performance evaluation of the fracturing system with reference to SY / T6376-2008. The viscosity was measured at 80°C and 160°C for 30 minutes to evaluate its temperature resistance. The viscosity at 120°C for 120 minutes was measured to evaluate its shear resistance. The sedimentation velocity of sand in the fracturing fluid was measured by the static suspension method to evaluate its sand carrying performance. 2.5g of the commercially available Shuangcheng 0249 breaker was added to the fracturing system and allowed to stand for 40 minutes at 80°C. The breaker performance was evaluated by the residue content of the fracturing system. The test results are shown in Table 1. Test results table:

[0068] Table 1 Test results

[0069] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Viscosity after shearing at 80℃ for 30min (mPa∙s) 217.66 219.10 224.40 134.56 197.10 157.54 Viscosity after shearing at 160℃ for 30min (mPa∙s) 92.57 93.02 97.82 46.50 84.90 57.80 Viscosity after shearing at 120℃ for 120min (mPa∙s) 101.06 101.37 102.50 63.24 152.32 77.43 Sedimentation velocity (cm / s) 0.028 0.027 0.024 0.058 0.030 0.047 Residue content (mg / L) 308.9 308.0 307.6 324.7 310.2 319.5

[0070] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces the composite guar gum with modified guar gum in the preparation process of the zwitterionic fracturing thickener in Example 3. Due to the lack of lipoic acid groups, the formation of its micro-crosslinked network is weakened, which leads to a significant decrease in its heat resistance and shear resistance. Comparative Example 2 replaces the intermediate 2 in the preparation process of the modified guar gum in Example 3 with 2,5-dimercaptothiadiazole. Due to the lack of zwitterions, its sand carrying performance is greatly reduced.

[0071] In Comparative Example 3, the composite cross-linking agent in the preparation process of the zwitterionic fracturing thickener in Example 3 was replaced with a mixture of titanium oxide and molybdenum disulfide. Since the mixture lacked a special structure of bonding, its various properties were greatly reduced.

[0072] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0073] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a zwitterionic fracturing thickener, characterized in that: The method comprises the following steps: weighing the following raw materials in weight percentage: 35-40% carboxymethyl guar gum, 5-8% carboxymethyl hydroxypropyl guar gum, 15-20% composite guar gum and 6-8% composite cross-linking agent, and the balance being water, and mixing the carboxymethyl guar gum, carboxymethyl hydroxypropyl guar gum, composite guar gum, composite cross-linking agent and water to prepare a zwitterionic fracturing thickener; The composite guar gum is prepared by the following steps: Step A1: Mix cardanol, sodium hydroxide solution, tetrabutylammonium bromide and toluene, stir at a stirring rate of 150-180 rpm and a temperature of 70°C, add epichlorohydrin, and react for 4-6 hours to obtain intermediate 1; mix guar gum, sodium hydroxide solution and anhydrous ethanol, stir at a stirring rate of 80-120 rpm and room temperature for 20 minutes, add intermediate 1, and heat to 70°C and react for 6-8 hours to obtain grafted guar gum; Step A2: 2,5-dimercaptothiadiazole and ethyl acetate are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 100°C, 1,3-propane sultone is added, and the mixture is reacted for 24 hours to obtain intermediate 2; intermediate 2, grafted guar gum, ethanol and deionized water are mixed, stirred at a stirring rate of 60-80 rpm and room temperature, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is added, and the mixture is reacted for 12 hours under light conditions to obtain modified guar gum; Step A3: Modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and dimethyl sulfoxide are mixed, stirred at a stirring rate of 120-150 rpm and room temperature, and lipoic acid is added, and the mixture is reacted for 24 hours to obtain composite guar gum; The composite cross-linking agent is prepared by the following steps: Step B1: Mix silica nanospheres and anhydrous ethanol and ultrasonically disperse for 30 minutes, stir and add ammonia solution and tetrabutyl titanate at a stirring rate of 150-180 rpm and a temperature of 45°C, and react for 24 hours to obtain precursor 1, and mix precursor 1, hexadecyltrimethylammonium bromide and deionized water, stir for 12 hours at a stirring rate of 120-150 rpm and a temperature of 60°C to obtain precursor 2; Step B2: Precursor 2, sodium molybdate dihydrate, thioacetamide and deionized water are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 60°C for 12 hours, and then heated to 220°C and continued to react for 24 hours to obtain precursor 3. Precursor 3 is mixed with deionized water and ultrasonically dispersed for 20 minutes. At a stirring rate of 120-150 rpm and room temperature, sodium hydroxide solution is added and stirred for 6-8 hours to obtain precursor 4. Precursor 4 is calcined at 600°C for 2 hours to obtain a composite cross-linking agent.

2. The method for preparing a zwitterionic fracturing thickener according to claim 1, characterized in that: In step A1: the mass fraction of sodium hydroxide solution is 30%, and the amount ratio of cardanol, sodium hydroxide solution, tetrabutylammonium bromide and epichlorohydrin is 0.02-0.022 mol: 3-3.2 mL: 0.12-0.13 g: 0.022-0.024 mol; the mass fraction of sodium hydroxide solution is 30%, and the amount ratio of guar gum, sodium hydroxide solution and intermediate 1 is 10-12 g: 6-8 mL: 0.02-0.022 mol.

3. The method for preparing a zwitterionic fracturing thickener according to claim 1, characterized in that: In step A2, the amount ratio of 2,5-dimercaptothiadiazole, ethyl acetate and 1,3-propane sultone is 0.02-0.022 mol: 30-34 mL: 0.045-0.048 mol; the amount ratio of intermediate 2, grafted guar gum and 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone is 12-13 g: 0.01-0.011 mol: 0.8-1 g.

4. The method for preparing a zwitterionic fracturing thickener according to claim 1, characterized in that: In step A3, the ratio of modified guar gum, 4-dimethylaminopyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and lipoic acid is 12-13 g: 5-6 g: 8-10 g: 0.01-0.012 mol.

5. The method for preparing a zwitterionic fracturing thickener according to claim 1, characterized in that: In step B1: the mass fraction of the ammonia solution is 25%, the amount ratio of silica nanospheres, ammonia solution and tetrabutyl titanate is 0.3-0.4g:1.2-1.4mL:3.8-4mL; the amount ratio of precursor 1 and hexadecyltrimethylammonium bromide is 0.4-0.5g:0.16-0.2g.

6. The method for preparing a zwitterionic fracturing thickener according to claim 1, characterized in that: In step B2: the amount ratio of precursor 2, sodium molybdate dihydrate and thioacetamide is 0.3-0.4g: 0.12-0.13g: 0.13-0.14g; the mass fraction of sodium hydroxide solution is 15%, and the amount ratio of precursor 3 and sodium hydroxide solution is 0.4-0.45g: 3-4mL.

Citation Information

Patent Citations

  • Fracturing fluid which resists temperature of 200 DEG C

    CN102367380A

  • Guar gum grafted copolymer nanocomposite gel fracturing fluid and preparation method thereof

    CN112111264A